PENGARUH PEMANFAATAN MEDIA SOSIAL FACEBOOK TERHADAP PERILAKU BERPACARAN REMAJA PADA SISWA SMP - Nur, Atmadiah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis study aims to determine the effect of facebook social media utilization on the behavior of teenager dating to students of class VIII SMP Negeri 1 Sungai Raya Year 2017. The method used was descriptive method in form of correlations study . The population in this study is all students of class VIII. Then the sample was 68 students. Data collection techniques used is technique indirect communication and data collection tools are questionnaires. Data analysis technique using the formula percentage and poduct moment using SPSS version 16 then continued with coefficient of determination. From data analysis the researcher found that the utilization of social media facebook reached 77.19%, included in the good category. While dating behavior reached 74.85% in the category of enough. So the influence of utilization of facebook social media on dating behavior was 49.84%, meaning 51.16% dating behavior was influenced by others variable that was not found in this study. Keywords : Social Media, Facebook, Dating Behavior